The role of the SGK3/TOPK signaling pathway in the transition from acute kidney injury to chronic kidney disease - Shu, Huapan; Wang, Yumei; Zhang, Hui; Dong, Qingqing; Sun, Lulu; Tu, Yuchi; Liao, Qianqian; Feng, Li; Yao, Lijun (Frontiers in Pharmacology, 2023)
Introduction: Profibrotic phenotype of renal tubular epithelial cells (TECs) featured with epithelial to mesenchymal transition (EMT) and profibrotic factors secretion, and aberrant accumulation of CD206+ M2 macrophages are the key points in the transition from acute kidney injury (AKI) to chronic kidney disease (CKD). Nevertheless, the underlying mechanisms involved remain incompletely understood. Serum and glucocorticoid-inducible kinase (SGK) is a serine/threonine protein kinase, required for intestinal nutrient transport and ion channels modulation. T-LAK-cell-originated protein kinase (TOPK) is a member of the mitogen activated protein kinase family, linked to cell cycle regulation. However, little is known about their roles in AKI-CKD transition. Methods: In this study, three models were constructed in C57BL/6 mice: low dose and multiple intraperitoneal injection of cisplatin, 5/6 nephrectomy and unilateral ureteral obstruction model. Rat renal tubular epithelial cells (NRK-52E) were dealt with cisplatin to induce profibrotic phenotype, while a mouse monocytic cell line (RAW264.7) were cultured with cisplatin or TGF-β1 to induce M1 or M2 macrophage polarization respectively. And co-cultured NRK-52E and RAW264.7 through transwell plate to explore the interaction between them. The expression of SGK3 and TOPK phosphorylation were detected by immunohistochemistry, immunofluorescence and western blot analysis. Results:In vivo, the expression of SGK3 and p-TOPK were gradually inhibited in TECs, but enhanced in CD206+ M2 macrophages. In vitro, SGK3 inhibition aggravated epithelial to mesenchymal transition through reducing the phosphorylation state of TOPK, and controlling TGF-β1 synthesis and secretion in TECs. However, SGK3/TOPK axis activation promoted CD206+ M2 macrophage polarization, which caused kidney fibrosis by mediating macrophage to myofibroblast transition (MMT). When co-cultured, the TGF-β1 from profibrotic TECs evoked CD206+ M2 macrophage polarization and MMT, which could be attenuated by SGK3/TOPK axis inhibition in macrophages. Conversely, SGK3/TOPK signaling pathway activation in TECs could reverse CD206+ M2 macrophages aggravated EMT. Discussion: We revealed for the first time that SGK3 regulated TOPK phosphorylation to mediate TECs profibrotic phenotype, macrophage plasticity and the crosstalk between TECs and macrophages during AKI-CKD transition. Our results demonstrated the inverse effect of SGK3/TOPK signaling pathway in profibrotic TECs and CD206+ M2 macrophages polarization during the AKI-CKD transition.